Gastroschisis Associated with Lower Limb and Spinal Congenital Anomalies - Dharmraj, Meena (Medknow Publications & Media Pvt Ltd, 2012)
Gastroschisis is not a very rare congenital deformity, but extragastrointestinal association is rare, if any present, in that condition, an alternative diagnosis should be considered, like Pentalogy of Cantrell, Limb-body wall complex, etc., Other birth defects are always associated with gastroschisis, most commonly, abnormalities of the cardiac and genitourinary. The present case is one of the gastroschisis to highlight the associations of spinal and lower limbs anomalies, with two-vessel short umbilical cord and severe oligohydramnios in primiparous.